A Biomechanical Analysis of Peroneus Brevis Split Lesions, Repair, and Partial Resection. (May 2022) - Trache, Tudor; Camenzind, Roland S.; Bachmann, Elias; Viehöfer, Arnd; Jud, Lukas; Wirth, Stephan; Imhoff, Florian B.
Background: Peroneus brevis tendon tears are associated with chronic ankle pain and instability following sprain injuries. The aim of this study is to elucidate the biomechanical changes induced by a peroneus brevis split and surgical treatment by tubularizing suture or partial resection. Methods: Nine human lower leg specimens were biomechanically tested. Preexisting tendon pathology was ruled out by magnetic resonance imaging and histology. Specimens were subjected to sequential testing of 4 conditions of the peroneus brevis tendon: (1) native, (2) longitudinal lesion, (3) tubularizing suture, and (4) 50% resection. The outcome parameters were the tendon stiffness (N/mm) and the length variation of the split portion at 5 N load. Results: The median specimen age at death was 55.8 years (range 50-64 years). The longitudinal tendon split led to an elongation by 1.21 ± 1.15 mm, which was significantly reduced by tubularizing suture to 0.24 ± 0.97 mm ( P = .021). Furthermore, 50% resection of the tendon elongated it by a mean 2.45 ± 1.9 mm ( P = .01) and significantly reduced its stiffness compared to the intact condition (4.7 ± 1.17 N/mm, P = .024) and sutured condition (4.76 ± 1.04 N/mm, P = .011). Conclusion: Longitudinal split and 50% resection of the peroneus brevis tendon led to elongation and loss of tendon stiffness. These properties were improved by tubularizing suture. The significance of these changes in the clinical setting needs further investigation. Clinical Relevance: Tubularizing suture of a peroneus brevis split can restore biomechanical properties to almost native condition, potentially aiding ankle stability in symptomatic cases. A split lesion and partial resection of the tendon showed reduced stiffness and increased elongation.